Sosialisasi Social Preuneur Bagi Kelompok PKK Kecamatan Bangkala Kabupaten Jeneponto - Herlina Sakawati; Muhammad Nur Yamin; Novayanti Sopia Rukmana; Sirajuddin Saleh; widyawati widyawati; Asri Nur Aina; Sulmiah Sulmiah (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Social Preunur is an entrepreneurial approach to solving social problems. The problem found in the community, especially in Jeneponto Regency, is poverty. The PKK group is a group that has roles as motivators, facilitators, planners, implementers, controllers, and movers with the target family in rural areas. Therefore, this counseling is targeted at the PKK Women Group so that they can implement social preunurship in Bangkala District. The problems found in the field are first, the motivation of PKK mothers is still very lacking. The motivation in question is motivation in entrepreneurship and business management; second, apart from the mindset in their thinking that they work is to become workers on the other side as job providers. The method used is lecture, discussion, demonstration, and question and answer. Through this service activity, it is hoped that the participation of PKK mothers will be involved in alleviating poverty by playing a role in improving the family economy and being able to take advantage of the surrounding community as the concept of social preneur